Geronimo Stilton #02 : The Curse of the Cheese Pyramid - Stilton, Geronimo (Scholastic, 2004)
Geronimo travels to Egypt to interview Professor Alrat Spitfur and learns the secret of the Seven Wonders of the Ancient Mouse World.